Blood pressure targets, medication consideration and unique concerns in elderly hypertension IV: Focus on frailty, orthostatic hypotension, and resistant hypertension - Po-Sheng Wu; Chia-Ter Chao; Chien-Hao Hsiao; Chiu-Fen Yang; Ying-Hsiang Lee; Hung-Ju Lin; Chih-Fan Yeh; Long-Teng Lee; Kuo-Chin Huang; Meng-Chih Lee; Cheng-Kuo Huang; Yen-Hung Lin; et al. (Journal of the Formosan Medical Association, 2025)
Hypertension increases the risk of cardiovascular disease in the elderly. Although treating hypertension can reduce the risk of cardiovascular disease and its related mortality, it is also challenging because these patients could have frailty, orthostatic hypotension (OH) and resistant hypertension (RHTN), which makes them more susceptible to treatment-related adverse events. Identifying such patients and tailoring the choice of drugs and blood pressure targets is crucial to balance the harms and benefits. The Clinical Frailty Scale is recommended to assess elderly patients with hypertension and frailty. For very frail patients, unnecessary medications should be deprescribed to avoid adverse events. Hypertension and OH frequently co-occur in the elderly, and recognizing and managing OH is essential to prevent falls and adverse events. The management of blood pressure in elderly patients with frailty, OH, and RHTN is complex, requiring the patients, their family and caregivers to be involved in decision-making to ensure that treatment plans are well-informed and aligned with the patient's needs.